Critical Response to "A Short History of K-12 Public School Spending in British Columbia" - Laitsch, Dan; Malcolmson, John; Kuehn, Larry (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
In Issue 196 of the Canadian Journal of Educational Administration and Policy (CJEAP), the journal published an article by Jason Ellis, A Short History of K-12 Public School Spending in British Columbia, 1970-2020 that claimed “K-12 public education spending in British Columbia – adjusted for inflation – is 250 percent higher in 2020 than it was in 1970” (Ellis, 2021, p. 102). We illustrate how this claim lacks a theoretical framework, is based on weak data sources, a flawed research method and skewed analysis that results in a misleading understanding of resource allocations in BC. We present alternative ways to understand spending on education in BC in an effort to correct the scholarly and public record.